2002
DOI: 10.3732/ajb.89.12.2007
|View full text |Cite
|
Sign up to set email alerts
|

Glacial history of the alpine herb Rumex Nivalis (Polygonaceae): a comparison of common phylogeographic methods with nested clade analysis

Abstract: The glacial history of the alpine herb Rumex nivalis was investigated using amplified fragment length polymorphisms (AFLPs) and restriction fragment length polymorphisms with polymerase chain reaction (PCR-RFLPs) of cpDNA. Both traditional statistical methods widely applied in phylogeographic research and nested clade analysis were used. The AFLPs indicated little geographic structure probably due to the wind-pollinated reproductive system of the dioecious R. nivalis. Because cpDNA haplotypes exhibited distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
2
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(97 citation statements)
references
References 40 publications
(50 reference statements)
3
91
2
1
Order By: Relevance
“…Thus, AFLPs indeed proved to be a powerful method to detect male-specific fragments in this sexually heterogametic and heteromorphic species and, at the same time, they were a useful starting point for the development of SCAR primers. The potential of AFLPs to produce a high number of fragments (Vos et al 1995) and, therefore, an increased chance to detect character-linked markers, is reflected in the fact that the source of the present development of male-specific markers in R. nivalis was a side-product of its phylogeographic investigation (Stehlik 2002).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, AFLPs indeed proved to be a powerful method to detect male-specific fragments in this sexually heterogametic and heteromorphic species and, at the same time, they were a useful starting point for the development of SCAR primers. The potential of AFLPs to produce a high number of fragments (Vos et al 1995) and, therefore, an increased chance to detect character-linked markers, is reflected in the fact that the source of the present development of male-specific markers in R. nivalis was a side-product of its phylogeographic investigation (Stehlik 2002).…”
Section: Resultsmentioning
confidence: 99%
“…in Central and southeastern Europe (Wagenitz 1981). In a previous AFLP analysis (Stehlik 2002), some fragments were tentatively identified as sex-specific. One of these fragments was especially intense and present in all male plants (N=80).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Climate cycles may therefore have led currently isolated populations to have come repeatedly into contact during cold periods as their suitable habitat expanded. For the alpine flora, long-term refugia within the Alps and at their northern, southern and eastern borders have been proposed on the basis of recent molecular studies (Stehlik et al, 2001;Stehlik, 2002;Schönswetter et al, 2005). Such results have important implications for the community ecology of montane habitats.…”
Section: Introductionmentioning
confidence: 99%
“…Results were similar for Hypericum nummularium L. populations in the Alps, which were not true in the Pyrenees, 19 Also, in Eryngium alpestris Schultes populations, no significant correlation was found at a geographical distance of 250 km, 47 while in a study on Rumex nivalis Hegetschw, a correlation was found only in a large region of Switzerland. 48 Results from cluster analysis of single data sets were less related to geographical distribution. In fact, we found that the myb marker was more adept at differentiating species while NBS markers were best for discriminating populations.…”
Section: Discussionmentioning
confidence: 99%